Taking Stock: Marie Nimier’s Textual Cabinet of Curiosities - Adrienne Angelo (Studies in 20th & 21st Century Literature, 2014)
In many life-writing projects, the seemingly innocuous description of heteroclite objects and how those objects are stored and recalled in fact plays an important role in demonstrating their importance to the process of memory work. At once the lingering traces of one’s past and also an aggregation of stories evoked by an examination of them, these curios focus attention on the relationship between the individual and the storage of memories. This article will focus on certain collectibles, collections and collectors that appear throughout the fictional, autobiographical and autofictional world that Marie Nimier has scripted to date. This textual cabinet of curiosities and the act of collecting more generally serve as a trope to connect memory with materiality, despite the numerous narrative voices that Nimier assumes—voices that move from a first-person “Marie Nimier” to an unnamed, although clearly identifiable first-person and even float between genders. Despite this nominal and narrational fluidity, objects function to guarantee recognition, both for the reader, and, especially, for the author herself. What is at stake in this intertextual assemblage of objects is not only the roles that they play in allowing the narrator to revisit past traumas and loss, but also in connecting the author’s presence to other, more fictionalized voices that above all signify the primacy of life-writing in her corpus.
Keywords: Marie Nimier; life-writing; memory; collections